2015
DOI: 10.1186/s12916-015-0375-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child health nurse screening and care for mothers experiencing domestic violence (MOVE): a cluster randomised trial

Abstract: BackgroundMothers are at risk of domestic violence (DV) and its harmful consequences postpartum. There is no evidence to date for sustainability of DV screening in primary care settings. We aimed to test whether a theory-informed, maternal and child health (MCH) nurse-designed model increased and sustained DV screening, disclosure, safety planning and referrals compared with usual care.MethodsCluster randomised controlled trial of 12 month MCH DV screening and care intervention with 24 month follow-up.The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(136 citation statements)
references
References 27 publications
7
128
0
1
Order By: Relevance
“…Recent research shows that outcomes, such as safety planning with women may be sustained when using comprehensive, system‐level interventions based on implementation theory (Taft et al . ). Although no additional training was included in this study, authors acknowledged the importance of ongoing education and reflective practice to improve and maintain nursing skills (Hooker et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent research shows that outcomes, such as safety planning with women may be sustained when using comprehensive, system‐level interventions based on implementation theory (Taft et al . ). Although no additional training was included in this study, authors acknowledged the importance of ongoing education and reflective practice to improve and maintain nursing skills (Hooker et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Taft et al . ). A lack of IPV education for healthcare practitioners has been identified as a major barrier to adequate recognition and care for women experiencing IPV (Sprague et al .…”
Section: Introductionmentioning
confidence: 97%
“…This was in spite of a thorough implementation, training and access to guidance throughout the period [8]. Taft et al found similar screening numbers among maternal and child health nurses in Australia [37]. …”
Section: Discussionmentioning
confidence: 99%
“…To examine the help‐seeking patterns in abused and non‐abused postpartum women, we analysed data from the MOVE (Improving Maternal and Child Health Care for Vulnerable Mothers) trial. MOVE was a cluster randomised control trial which aimed to enhance the identification and support of postpartum women who may have experienced partner violence (Taft et al, ). The trial was set in eight Victorian MCH services within local government, in metropolitan Melbourne, Victoria, Australia.…”
Section: Methodsmentioning
confidence: 99%